Genotoxicity of Ciprofloxacin in Bone Marrow Stem Cells of Mice Infected with Uropathogenic E. coli - Muthana Ibrahim Maleek (Journal of Global Pharma Technology, 2018)
Background and Objectives: Ciprofloxacin is an antibiotic used for the treatment of uropathogenic Escherichia coli (UPEC) infections. It is intended in this study to investigate the genotoxic effects of ciprofloxacin on bone marrow stem cells of mice prior to and after infection with E. coli. Method: Two groups of mice were injected intraperitoneally every 8 hours with 9.5 mg/kg Ciprofloxacin; the first was for 24 hours and the other was for 5 days. Similarly, two other groups of mice were injected with 0.5 ml (1.5×108 cfu/ml) E. coli and treated with ciprofloxacin for 5 days. Microscopic slides were prepared from bone marrow of treated mice and genotoxicity was assessed by counting the number of chromosomes aberrations (CAs), mitotic index (MI) and micronucleus (MN). Results and Interpretation: Significant increase in the number of CAs, a decrease in MI and insignificant change in number of MN were seen in mice infected with E. coli and treated for 5 days with ciprofloxacin. However, no change in the values of these aberrations was observed in mice treated for 24 hours. It is believed that the effects of Ciprofloxacin on DNA in combination with the accumulated effects of E. coli toxins were responsible for the observed DNA damages. Conclusion: The use of ciprofloxacin for the treatment of E. coli infection may increase genotoxicity in bone marrow stem cells, which produces significant DNA damage. Keywords: Ciprofloxacin, E. coli, Stem cells, Mitotic index, Chromosomal aberrations, Micronuclei.